2023
DOI: 10.1002/ptr.7806
|View full text |Cite
|
Sign up to set email alerts
|

Berberine and health outcomes: An umbrella review

Abstract: Berberine is a plant extract widely used in clinical practice. This review aimed to summarize and to grade the available evidence on the association between berberine consumption and health-related outcomes. The PubMed, Cochrane Library, and Embase databases were searched for meta-analyses of randomized controlled trials (RCTs) assessing the efficacy and safety of berberine from inception to June 30, 2022. The AMSTAR-2 and GRADE system were used to assess the methodological quality and evidence level of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…(iii) Detailed information on Ber's mode of action, in comparison to archetypical c-I inhibitors, was obtained on the transcriptome and metabolome level. The redox-active compound was considered of high interest, as it emerged recently as a nutraceutical ingredient of food supplements meant to counteract aging and several diseases [89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Detailed information on Ber's mode of action, in comparison to archetypical c-I inhibitors, was obtained on the transcriptome and metabolome level. The redox-active compound was considered of high interest, as it emerged recently as a nutraceutical ingredient of food supplements meant to counteract aging and several diseases [89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the value of FITC-A in the CuO@BER/BH group was significantly lower than that of the BH group, which could be attributed to the antioxidant activity of BER. 14 It has been reported that the control of ROS level could alleviate the oxidative damage at the wound site, promote the proliferation of epithelial cells, angiogenesis, and tissue restoration; therefore, the antioxidant activity of CuO@BER/BH hydrogel was beneficial to the wound healing. 63 The increase in the number of M1 macrophages and neutrophils in chronic wound sites is closely related to the elevated levels of ROS, chemokines, and cytokines, and these factors mutually promote the inflammation, forming a constant vicious cycle 64 and hindering wound healing.…”
Section: Water Content and Swellingmentioning
confidence: 99%
“…Berberine (BER) is an isoquinoline alkaloid and exhibits a range of pharmacological activities, including antibacterial, anti-inflammatory, antioxidant, and regulation of glucose and lipid metabolism. 14 These properties make it a promising candidate for alleviating inflammation and oxidative stress in DU. Interestingly, it has been reported that the combination of metal NPs with BER achieved enhanced photothermal performance, resulting in the improved antibacterial and antitumor efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The osteoblast-like phenotype, also called "calcified," is responsible for the active intracellular calcium deposition and extracellular matrix mineralization (Demer and Tintut, 2008). The lack of effective treatments has pushed research efforts towards natural extractsderived molecules such as Quercetin (Anand David et al, 2016;Ceccherini et al, 2020;Aghababaei and Hadidi, 2023) and Berberine (Ai et al, 2021;Li et al, 2023) for their anti-inflammatory and antioxidant activity exerted in a broad variety of human pathologies, including cardiovascular diseases. Berberine is an isoquinoline alkaloid possessing ameliorative effects in experimental mouse models of VC by activating the Akt signaling pathway, and inhibiting either endoplasmic reticulum stress or inflammatory reaction (Li et al, 2022;Xiao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%